Hubungan Asupan Energi, Aktivitas Fisik, dan Tingkat Stres dengan Status Gizi Santri di Asrama Sunan Ampel Putri Pondok Pesantren Mamba’ul Ma’arif Denanyar Jombang - Dini Lubna Alyani (Lembaga Pengembangan Kinerja Dosen, 2024)
Nutritional problems in adolescents still occur in Indonesia, one of the problems is the incidence of undernutrition and overnutrition. Rapid growth (grow spurt) occurs during adolescence, so it is necessary to pay attention to the nutrients it consumes. The purpose of this study was to analyze the relationship between energy intake, physical activity, and stress levels with nutritional status in female santri of Sunan Ampel Dormitory, Mamba'ul Ma'arif Islamic Boarding School Denanyar Jombang. This study is a correlational study using a Cross-Sectional design. The research sample amounted to 63 santris obtained by purposive sampling method. Data were collected directly using a 2x24 hour food recall questionnaire to obtain energy intake data, the International Physical Activity Questionnaire - Short Form (IPAQ-SF) questionnaire to obtain physical activity data, the Kessler Psychological Distress Scale (KPDS) questionnaire to obtain stress level data, and anthropometric data measurements to obtain nutritional status data. Data analysis used the Fisher Exact Test. The results showed that: 1) there is a relationship between energy intake and nutritional status, 2) there is no relationship between physical activity and nutritional status, and 3) there is no relationship between stress levels and nutritional status. Suggestions in this study for female santri of Sunan Ampel Denanyar Jombang Dormitory to be more concerned about maintaining healthy food intake patterns by paying attention to the amount, type and frequency of food consumed. and sufficient physical activity to maintain normal nutritional status and prevent adverse health risks.